Unpacking the Entrepreneurship Education Conundrum: Lecturer Competency, Curriculum, and Pedagogy - Chux Gervase Iwu; Eugine Tafadzwa Maziriri; Lucky Sibanda; Tendai Makwara (Administrative Sciences)
This qualitative study explores the complex landscape of entrepreneurship education by focusing on lecturer competency, entrepreneurship curriculum, and pedagogy. This study addresses critical gaps in the current literature by investigating key questions: ideal instructional approaches for entrepreneurship, essential components of the curriculum, providers of entrepreneurial knowledge, and overarching strategies to foster entrepreneurship in higher education. Employing the Gioia methodology, this research adopted a qualitative inductive approach by collecting data from 14 participants actively engaged in entrepreneurship education and development across various South African universities. The findings highlight the diverse perspectives of academics and underscore the importance of collaborative and interactive teaching methods in preparing students for entrepreneurial challenges. This research contributes valuable insights to inform policy and practice in enhancing entrepreneurship education within South African higher education institutions (HEIs).